Zinc Oxide Nanomaterial-Based Dispersive Solid Phase Extraction for the Trace Determination of Gold in Flash Gold Plating Solution Samples using Flame Atomic Absorption Spectrophotometry - Kapukiran, Fatih; Kartoglu, Bedrihan; Ebrar Karlidag, Nazime; Bakirdere, Sezgin (WILEY-V C H VERLAG GMBH, 2023)
The noble metal Au is extensively used in jewelry, industry, and medicine. In order to mitigate the low sensitivity of the flame module atomic absorption spectrometer (FAAS) to determine the gold, zinc oxide (ZnO) nanomaterial were synthesized and used to pretreatment of the sample and preconcentrate gold ions in dispersive solid phase extraction (DSPE) process. Enrichment factor of the extraction method was enhanced by performing buffer solution type/volume, nanomaterial amount, mixing type/period, and desorption solvent concentration/volume optimizations. Calibration plot displayed good linearity and percent relative standard deviation recorded for the lowest concentration of the plot was adequately low (<7.0 %). Dynamic dynamic range for the proposed method was calculated between 30-400 & mu;g/L. Regression coefficient (R-2) of proposed method was found to be 0.9956. With an enrichment factor of 44.5-folds, method recorded a detection limit (LOD) of 7.4 & mu;g L-1 and quantification limit (LOQ) of 24.8 & mu;g L-1. Flash gold plating bath solution was used to certify the quantification accuracy/applicability in complex matrix of the method. The obtained results (1.86 & PLUSMN;0.08 g L-1) were compatible with the results of the reference method (ICP-OES) (1.87 & PLUSMN;0.08 g L-1). This is the first study for the extraction/preconcentration of gold using ZnO nanomaterial.
Keywords: Nanomaterial; Precious metal; Preconcentration; Spectrophotometry; LIQUID-LIQUID MICROEXTRACTION; SPECTROMETRIC DETERMINATION; SELECTIVE DETERMINATION; ENVIRONMENTAL-SAMPLES; SILICA-GEL; PALLADIUM; SEPARATION; ADSORBENT; GOLD(III); Chemistry